2017
DOI: 10.1093/jamia/ocx123
|View full text |Cite
|
Sign up to set email alerts
|

Ethical issues in the use of SMS messaging in HIV care and treatment in low- and middle-income countries: case examples from Mozambique

Abstract: The introduction of mobile communication technologies in health care in low- and middle-income countries offers an opportunity for increased efficiencies in provision of care, improved utilization of scarce resources, reductions in workload, and increased reach of services to a larger target population. Short message service (SMS) technologies offer promise, with several large-scale SMS-based implementations already under way. Still largely lacking in the research literature are evaluations of specific ethical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…While phones were provided to participants in many early SMS studies, it is increasingly less common to do so as frequency of phone ownership has increased [ 35 ] and due to concerns that phone provision may not increase participation if phones may be sold or used for other purposes [ 55 ]. As a result, phone provision was not determined to be a scalable or sustainable approach to digital health programs [ 39 , 56 ]. However, in areas where mobile phones and SMS literacy are not ubiquitous, SMS engagement may be sub-optimal [ 57 ] and training can result in substantial start-up costs and delays [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…While phones were provided to participants in many early SMS studies, it is increasingly less common to do so as frequency of phone ownership has increased [ 35 ] and due to concerns that phone provision may not increase participation if phones may be sold or used for other purposes [ 55 ]. As a result, phone provision was not determined to be a scalable or sustainable approach to digital health programs [ 39 , 56 ]. However, in areas where mobile phones and SMS literacy are not ubiquitous, SMS engagement may be sub-optimal [ 57 ] and training can result in substantial start-up costs and delays [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ossemane and colleagues discuss two SMS interventions in Mozambique that work to improve the retention of HIV+ patients in treatment. 33 Interestingly, given that telemedicine is often implemented to reach those in rural areas, one of these interventions found success in urban patients but not rural patients. 34 It must be noted, however, that just because a telemedical service is effective in general it is not necessarily effective in all situations.…”
Section: Effectivenessmentioning
confidence: 99%
“…A recent addition to research effort in SSA is mobile phone usage for collecting and sending research data. How the data are used and other ethical issues are in the early stages of study as reported by Ossemane and colleagues [64]. Also, online data collection and storage methods such as REDCap (which may be institution-based in the West as well as in Africa) [65] focus attention on the issue of data ownership and how data are used.…”
Section: Justice and Autonomy-resource Utilization Including End-of-life Decision Makingmentioning
confidence: 99%